PRE-OPERATIVE DIAGNOSTIC CHALLENGE OF TORSION OF THE GALLBLADDER - Inge Kurniawati; . Jimmy; Wayan Periadijaya (Indoscholar, 2018)
Gallbladder torsion is a very rare clinical entity and a difficult condition to diagnose preoperatively. Since its first description in 1898 by Wendel, there have been over 500 documented cases in the literature. The pathophysiology is that of mechanical organo-axial torsion along the gallbladder’s longitudinal axis involving the cystic duct and cystic artery, and with a pre-requisite of local mesenteric redundancy. Gallbladder torsion typically presents as an acute abdomen requiringemergency surgery but the preoperative diagnosis of gallbladder torsion is difficult and most cases are found as a surprise at surgery. Consequently, a delay in diagnosis can have devastating patient outcomes. Herein we report a case of acute gallbladder torsion in an elderly Balinese woman and treated surgically. To our knowledge, this is the first reported case in Bali with a subsequent literature review on the management of this uncommon condition.